Determinants of Student Work Readiness: The Role of Internship Experience, Organizational Involvement, and Networking - Wijaya Agus Setiawan; Nurhadi (Jurnal Investasi Islam, 2026)
The increasing competitiveness of the modern labor market, driven by globalization and rapid technological change, has placed graduate work readiness as a pressing strategic concern in higher education. Despite extensive studies on internship and organizational experiences, limited research has examined the combined role of professional networking in shaping students' work readiness, particularly within the Indonesian higher education context. Grounded in Human Capital Theory and Social Capital Theory, this study analyzes the influence of Internship Experience, Organizational Involvement, and Networking on the work readiness of students at Universitas Pembangunan Nasional "Veteran" Jawa Timur. A quantitative associative design was employed, with data collected through questionnaires distributed to 154 students from the 2022 and 2023 cohorts via purposive and proportionate stratified random sampling, analyzed using multiple linear regression. The findings reveal that all three variables simultaneously exert a significant effect on work readiness (F = 33.851; p < 0.001). Partially, Internship Experience (t = 3.644; p < 0.001) and Networking (t = 5.984; p < 0.001) each demonstrate a positive and significant effect, while Organizational Involvement does not yield a significant effect (t = 1.346; p = 0.180), suggesting that organizational participation without substantive leadership roles and professional relevance may be insufficient to enhance work readiness. Networking emerges as the most dominant predictor (β = 0.524), underscoring a paradigm shift in graduate employability from human capital qualifications toward social capital competencies. The three variables collectively explain 39.2% of the variance in work readiness. This study contributes novelty by establishing networking as an independent and dominant predictor within a unified model, offering implications for universities, career centers, and industry stakeholders in designing programs that holistically develop graduate employability.